2011
DOI: 10.1039/c1cp00036e
|View full text |Cite
|
Sign up to set email alerts
|

Size and surface effects on the magnetic properties of NiO nanoparticles

Abstract: NiO nanoparticles (NPs) were prepared by a sol-gel process using the citrate route. The sol-gel parameters were tuned to obtain samples with different average particle sizes, ranging from 12 to 70 nm. Magnetic characterization revealed an increase in the blocking temperature with the diameter of the NPs and an increase in the effective magnetic anisotropy (K(eff)) with decreasing particle size. The magnetic moment per particle was calculated for all samples using the susceptibility value at T = 300 K. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(93 citation statements)
references
References 42 publications
12
78
0
Order By: Relevance
“…On the other hand, the strain in the pure NiO powder is quite low and almost comparable to the NiO powder prepared by chemical preparation techniques. 27,28 However, the milled powder exhibits quite large strain, which increases with increasing the milling speeds. At larger milling speed, the strain also tends to saturate.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the strain in the pure NiO powder is quite low and almost comparable to the NiO powder prepared by chemical preparation techniques. 27,28 However, the milled powder exhibits quite large strain, which increases with increasing the milling speeds. At larger milling speed, the strain also tends to saturate.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have been reported on particle size and morphology effects on magnetic properties of NiO prepared by various techniques, [7][8][9][10][11][12] but the results of the size effects on magnetic performance of NiO nanoparticles from different groups are inconsistent. 13,14 The inconsistent was considered due to the relatively large size distribution of particles with relatively irregular morphological.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology, crystallography and size of the nano-structured materials can greatly influence their optical, electronic, magnetic, and catalytic properties [2]. Among transition metal oxides, nickel oxide (NiO) bulk and nano size have received considerable attention due to their wide range of applications in different fields, such as: catalysis [3], fuel cell electrodes and gas sensors [4], electrochromic films [5], battery cathodes [6], magnetic materials [7], and photovoltaic devices [8]. Because of the quantum size and surface effects, NiO nanoparticles exhibit catalytic, optical, electronic, and magnetic properties that are significantly different than those of bulk-sized NiO particles [9].…”
Section: Introductionmentioning
confidence: 99%